Evaluation Of A Powder‐Free DNA Extraction Method For Skeletal Remains1. Issue 6 (7th February 2018) - Harrel, Michelle; Mayes, Carrie; Gangitano, David; Hughes‐Stamm, Sheree
Abstract: Bones are often recovered in forensic investigations, including missing persons and mass disasters. While traditional DNA extraction methods rely on grinding bone into powder prior to DNA purification, the TBone Ex buffer (DNA Chip Research Inc.) digests bone chips without powdering. In this study, six bones were extracted using the TBone Ex kit in conjunction with the PrepFiler ® BTA™ DNA extraction kit (Thermo Fisher Scientific) both manually and via an automated platform. Comparable amounts of DNA were recovered from a 50 mg bone chip using the TBone Ex kit and 50 mg of powdered bone with the PrepFiler ® BTA™ kit. However, automated DNA purification decreased DNA yield ( p < 0.05). Nevertheless, short tandem repeat (STR) success was comparable across all methods tested. This study demonstrates that digestion of whole bone fragments is an efficient alternative to powdering bones for DNA extraction without compromising downstream STR profile quality.